Population Estimation of Leafminer (Diptera: Agromyzidae) Associated with Successive Stages of Mung Bean Vigna radiate (Linn.) Wilczek - Thapa, Moon; Thapa, R.B. (Our Nature, 2006)
Present study deals with the Mung bean variety K851 cultivated at three locations of Biratnagar by designing an experiment randomized Block design. Flies reared from the successive stages of Mung bean plant were identified as: Melanogromyza sojae (Zehnther), internal stem and root feeder, Ophiomyia phaseoli (Tryon) external stem and root feeder and Liriomyza sativae Blanchard, Leaf mining one. Their field populations under natural condition were regulated by parasitic fauna and other mortality factors. Under certain conditions their population become high and cause economic loss. Population of these flies were found to be highest at seedling stages reaching up to the extent of 88.6% and it was found to decrease with the successive stage of plant growth reaching up to the extent of 0.56%. Keywords: Diptera, Agromyzidae, Population, Successive stage, RBD doi:10.3126/on.v2i1.319 Our Nature (2004) 2: 19-20